Bit-error probabilities of multicode direct-sequence spread-spectrum multiple-access systems. - Seung Joon Lee (IEEE Transactions on communications)
Many techniques for calculating bit-error probabilities (BEPs) of direct-sequence spread-spectrum multiple-access systems (DS-SSMA) have been reported. Among them are the following three techniques: (1) the standard Gaussian approximation; (2) the improved Gaussian approximation; (3) and the simplified improved Gaussian approximation. We extend these techniques to derive the BEPs of multicode DS-SSMA systems. We assess the three techniques by comparing their results with the result of computer simulation